Optimizing Asset Management: A Risk-Based Approach with Inventory Outsourcing and Asset Management Information System - Fajar, Muhammad Syaeful; Syaifuddiin, Gus Nanang; Hafidhoh, Nisa'ul; Ismar, MH. Ramdhani; Ivansyah, Maulana Nur (LPPM Universitas Andalas, 2023)
Effective management of regional assets is crucial for efficient government administration and community service delivery. Proper asset management ensures transparency, efficiency, and accountability in regional property management, supporting key tasks and functions of the government. Efficient asset management empowers local governments to fund regional development and enhances public confidence in state finance management. The rapid development of information technology presents unique challenges, especially in asset management within educational institutions. This study focuses on implementing the Risk-Based Asset Management (RBAM) method in a Web-Based Asset Management Information System. RBAM categorizes requests by risk levels, generates monthly data analysis, and aids in anticipating item stock quantities. The integrated RBAM is expected to enhance inventory management efficiency, improving responsiveness to demand fluctuations. This journal presents research findings related to RBAM implementation, aiming to enhance asset management performance in the government context. The study employs the Research and Development method, fitting for software engineering research. The development utilizes the waterfall model, ensuring a structured software development process. The system streamlines item data management, reporting requests, enhancing facility inventory management.